2017
DOI: 10.1097/md.0000000000009151
|View full text |Cite
|
Sign up to set email alerts
|

The comparison of acute toxicity in 2 treatment courses

Abstract: The most appropriate cisplatin treatment schedule delivered with radiotherapy in patients with head and neck squamous cell carcinoma (HNSCC) is unknown. The aim of this study was to compare the acute toxicity and its impact on the course of the treatment, administered cisplatin and radiation doses, the length of hospitalization and supportive drugs administration in patients with HNSCC receiving 2 different cisplatin treatment schedules administered with radiotherapy.In this retrospective analysis, 104 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Patients with oral tongue cancers may receive chemoradiation therapy after surgery to improve their survival [21,22]. Unfortunately, chemotherapy (i.e., cisplatin) and radiation may be associated with significant pain, such as severe neuropathies (4-71%), mucositis (26-41%), and dysphagia (12%), for which patients are treated with opioids, although with limited efficacy at the doses found in this study [6,[21][22][23][24][25][26]. Although Saraswathula et al found an association only between adjuvant radiotherapy and persistent postoperative opioid use and not with chemotherapy, Shah et al reported that patients with chemotherapy-induced peripheral neuropathies were twice as likely to receive opioids five years after treatment compared with those without the neuropathy [17,23].…”
Section: Discussionmentioning
confidence: 89%
“…Patients with oral tongue cancers may receive chemoradiation therapy after surgery to improve their survival [21,22]. Unfortunately, chemotherapy (i.e., cisplatin) and radiation may be associated with significant pain, such as severe neuropathies (4-71%), mucositis (26-41%), and dysphagia (12%), for which patients are treated with opioids, although with limited efficacy at the doses found in this study [6,[21][22][23][24][25][26]. Although Saraswathula et al found an association only between adjuvant radiotherapy and persistent postoperative opioid use and not with chemotherapy, Shah et al reported that patients with chemotherapy-induced peripheral neuropathies were twice as likely to receive opioids five years after treatment compared with those without the neuropathy [17,23].…”
Section: Discussionmentioning
confidence: 89%
“…The trial included mainly patients with oropharyngeal tumors (60%) (75). In a secondary analysis of the trial including only patients with larynx or hypopharynx tumors, there were no differences in laryngeal preservation, laryngectomy free survival, and overall survival (65). In general, the combination of cetuximab and radiotherapy is prescribed to patients unfit to receive cisplatin and radiotherapy, provided that several trials, mainly done in the scenario of HPV positive oropharynx cancer, demonstrated that cetuximab/RT was inferior to cisplatin/RT (76)(77)(78).…”
Section: Chemo-radiotherapy Combined With Other Anti-egfr Monoclonal mentioning
confidence: 99%
“…Concurrent irradiation and chemotherapy is the recommended regimen for locally advanced SCCHN patients (65). The current standard protocol of chemo-radiotherapy, involves the use of radiotherapy concurrent with cisplatin bolus dose of 100 mg/m 2 infused every 21 days (65). Despite the good results with this protocol, treatment-related toxicity remains an important concern.…”
Section: High Dose Chemotherapy Vs Low Dose Chemotherapy For Scchnmentioning
confidence: 99%
See 1 more Smart Citation
“…Existence of cancer stem cells [22,23], increased angiogenesis [24,25], and unfavorable immune profile in the microenvironment [26,27] are the proposed mechanisms that contribute to platinum-resistant OCSCC and predict poor prognosis. Moreover, the MTD of cisplatin (100 mg/m 2 ) is deemed as a highly toxic regimen because it has significant side-effects such as nephrotoxicity, ototoxicity, and neurotoxicity [28,29]. Therefore, novel therapeutic strategies are necessary to improve OCSCC treatment outcomes a step further [30].…”
Section: Introductionmentioning
confidence: 99%